1999
DOI: 10.1159/000018972
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome in Alcoholism – A Comparison of Self-Report and the Biological Markers Carbohydrate-Deficient Transferrin and γ-Glutamyl Transferase

Abstract: The primary source for evaluating treatment outcome in alcoholism is usually verbal self-report. Because the validity of self-report is often doubted, more objective markers for treatment outcome are needed. In this study, we compared self-report data from 238 male alcohol-dependent patients participating in a combined 6-week inpatient followed by a 1-year outpatient treatment program with the biological markers carbohydrate-deficient transferrin (CDT) and γ-glutamyl transferase (GGT). According to self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
1
14
0
5
Order By: Relevance
“…Testing of the data using a Friedman two-way analysis of variance also failed to indicate any significant effects (chi square values <1.5). From the fact that social drinkers and smokers did report significant craving in response to the present or analogous protocols (Mucha et al 1999), we see these data on desire for alcohol as further underscoring possible specific problems that alcoholics have in reporting information on alcohol (see Mundle et al 1999a).…”
Section: Resultssupporting
confidence: 55%
“…Testing of the data using a Friedman two-way analysis of variance also failed to indicate any significant effects (chi square values <1.5). From the fact that social drinkers and smokers did report significant craving in response to the present or analogous protocols (Mucha et al 1999), we see these data on desire for alcohol as further underscoring possible specific problems that alcoholics have in reporting information on alcohol (see Mundle et al 1999a).…”
Section: Resultssupporting
confidence: 55%
“…All patients were personally interviewed and all patients were well known by the interviewer (S.Y.). Several studies have shown a high validity and high reliability of self-report data of alcoholdependent patients in treatment compared to toxicologic analyses of blood or collateral informant reports (73,74). Other important limitation of the present study was that no scale were used to evaluate severity of anxiety and depressive symptoms, since they may be related with not only relapse (12,75,76), but also with HSM, HSA and defense styles.…”
Section: Discussionmentioning
confidence: 86%
“…Diese Befunde sind vergleichbar mit Ergebnissen anderer Studien zur Effizienz ambulanter wie stationärer Entwöh-nungstherapien. Es wurden Abstinenzquoten von ambulanten Therapien zum 6-Monats-Follow-up berichtet zwischen 34%-59% [4,23,24] und 48% zum 18-bis 24-Monats-Follow-up [35]. Studien mit vergleichbarer Katamnesedauer ergaben Abstinenzquoten zwischen 40-60% für stationäre Therapien [17].…”
Section: Nachuntersuchungunclassified
“…In einer kürzlich erschienenen Metaanalyse zur Frage der Therapieerfolge bei alkohol-und drogenabhängi-gen Patienten [31] konnten nur 3 Studien zu dieser Frage präsentiert werden, darunter die von uns früher durchgeführte Katamnese [23,35,38].Die Abstinenzquoten bewegten sich dabei bei einem Ausschöpfungsgrad von 66-78% zwischen 37% und 48% und waren damit durchaus vergleichbar mit den Ergebnissen stationärer Entwöhnungstherapien. Für den Bereich der teilstationären Entwöh-nungstherapie gibt es einige Erfahrungsberichte und Katamnesestudien von Tageskliniken aus der ehemaligen DDR.…”
Section: Untersuchungen Zur Effizienz Ambulanter Entwöhnungstherapienunclassified